Programmed Autophagy in the Fat Body of Aedes aegypti Is Required to Maintain Egg Maturation Cycles - Bryant, Bart (Public Library of Science, 2011)
Autophagy plays a pivotal role by allowing cells to recycle cellular components under conditions of stress, starvation, development and cancer. In this work, we have demonstrated that programmed autophagy in the mosquito fat body plays a critical role in maintaining of developmental switches required for normal progression of gonadotrophic cycles. Mosquitoes must feed on vertebrate blood for their egg development, with each gonadotrophic cycle being tightly coupled to a separate blood meal. As a consequence, some mosquito species are vectors of pathogens that cause devastating diseases in humans and domestic animals, most importantly malaria and Dengue fever. Hence, deciphering mechanisms to control egg developmental cycles is of paramount importance for devising novel approaches for mosquito control. Central to egg development is vitellogenesis, the production of yolk protein precursors in the fat body, the tissue analogous to a vertebrate liver, and their subsequent specific accumulation in developing oocytes. During each egg developmental cycle, the fat body undergoes a developmental program that includes previtellogenic build-up of biosynthetic machinery, intense production of yolk protein precursors, and termination of vitellogenesis. The importance of autophagy for termination of vitellogenesis was confirmed by RNA interference (RNAi) depletions of several autophagic genes (ATGs), which inhibited autophagy and resulted in untimely hyper activation of TOR and prolonged production of the major yolk protein precursor, vitellogenin (Vg). RNAi depletion of the ecdysone receptor (EcR) demonstrated its activating role of autophagy. Depletion of the autophagic genes and of EcR led to inhibition of the competence factor, betaFTZ-F1, which is required for ecdysone-mediated developmental transitions. Moreover, autophagy-incompetent female mosquitoes were unable to complete the second reproductive cycle and exhibited retardation and abnormalities in egg maturation. Thus, our study has revealed a novel function of programmed autophagy in maintaining egg maturation cycles in mosquitoes.